The transformed classic authors: Defoe and Dickens with their first appearances on the Bulgarian literary scene (Colloquia Comparativa Litterarum, 2025)
The article examines two of the first translations in modern Bulgarian language of works of fiction by English classical authors Daniel Defoe and Charles Dickens. Made from adaptations, they do not present their writers in full, but rather their Germanised and Russianised versions, which significantly change their reception. Attention is drawn to the problems of translation in the mid-19th century, as well as the fact that Young Robinson remains in manuscript, and the first translation of Dickens' A Christmas Carol was recognised as his work only at the beginning of this century due to the change in title.
Keywords: translation; adaptation; reception; Daniel Defoe; Charles Dickens